BJS.04PreciSSIon: A collaborative initiative to reduce incidence of SSI after elective colorectal surgery. (28th October 2021) - Clayphan, Benjamin; Biggs, Sarah; Dixon, Lauren; Jordan, Lesley; Dalton, Stephen; Pullyblank, Anne
Abstract: Aims: Surgical Site Infection (SSI) is common after colorectal surgery where rates are reported as high as 30%. The aim of this project was to assess whether a collaborative approach to implement a 4-point care bundle could reduce SSI rates across a group of hospitals. Methods: PreciSSIon is a Quality Improvement Project (QIP) involving 7 NHS hospitals, with a design based on the Institute for Healthcare Improvement's Breakthrough Series collaborative model. The Public Health England SSI surveillance questionnaire was used to measure patient-reported SSI at 30 days post-op. An evidence based bundle of care was introduced including: 2% chlorhexidine skin preparation; dual ring wound protectors; triclosan-coated sutures for wound closure; and a second dose of antibiotics after 4 hours. Results: All hospitals had implemented the care bundle by February 2020.  By December 2020 6/7 hospitals had reduced SSI. Mean patient questionnaire response rate = 84.8%. Mean compliance with each of the above bundle components are as follows: 91%; 72%; 85%; and 92% respectively. Conclusions: Implementing an evidence based care bundle, using a collaborative approach to QIP, was effective in reducing the rates of patient-reported SSI following colorectal surgery. The success of this project in the West of England suggests that similar methodology could be used to improve patient outcomes in other regions.